A Simplified Analytical Model to Evaluate Hospital Preparedness for Earthquake Emergency Response (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
Casualty management is crucial after an earthquake disaster. A comprehensive emergency response plan is essential for all sectors, especially in emergency healthcare services, to reduce the fatalities and maximize the number of saved lives after a mega-earthquake disaster. Post-earthquake emergency healthcare services greatly depend on the level of hospital preparedness. This research proposed a simplified analytical model to evaluate hospitals' preparedness for earthquake emergency response. The proposed model considers the number, severity, and distribution of injuries in the affected region, as well as the seismic vulnerability, hospitals' existing resources, and the timeline. The model can predict different levels of preparedness for different numbers of casualties and estimate the number of saved lives. In a case study of Dhaka Medical College Hospital, for damage state grades 1 and 2, a dynamic range of results have been discovered where a sufficient level of preparedness can be observed for a lower number and an insufficient level of preparedness for a higher number of casualties. In addition, we observed that prioritization of casualty treatment could significantly change the hospital preparedness level. Emergency managers and policymakers can utilize the proposed model to determine hospital preparedness levels and take the required actions to bridge the gap between post-earthquake hospital demand and capacity.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(1), 2022, P 53-68